PENGARUH TINGKAT LITERASI BACA SISWA TERHADAP EFEKTIVITAS PEMBELAJARAN - Yudho Ramafrizal S; Teni Julia Somadi (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2022)
The title of this study is the Effect of Student Reading Literacy Level on Learning Effectiveness (Survey on Introduction of Accounting Class X Accounting at SMK Negeri 3 bandung academic year 2021-2022). This research aims to (i) find out the level of student read literacy in Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung (ii) to know the level of learning effectiveness Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung (iii) knowing the magnitude of the influence of students' reading literacy levels on the effectiveness of learning in Introduction of Accounting of class X Accounting at SMK Negeri 3 bandung. In this study the authors used quantitative approach methods using survey research methods, with a population of 30. To seek influence, The data analysis used is a simple linear regression analysis using IBM SPSS Statistics Version 24.0,descriptive analysis ofreading literacy level with a weight of 37.97 and an average value of 3.80, and theeffectiveness of learning with a sum weight of 40.03 and an average value of 4.00, on a simple linear regression test there is a regression coefficient value obtained is 0.580, and the determination coefficient valueis obtained the number R (correlation coefficient) or the relationship number between variable X to variable Y of 0.557 or 55.7%. The amount of contribution made by the variable level of reading literacy can be seen from the number in R Square which is 0.310 which means that the level of reading literacy affects the effectiveness of learning by 31.0%. While the other 69.0% was influenced by other factors outside of the research conducted.